Open Letter to the International Criminal Court Alleging United Nations Complicity in Planetary Treason - Herndon, J. Marvin; Whiteside, Mark; Baldwin, Ian (Advances in Social Sciences Research Journal, 2022)
We provide a preponderance of evidence that worldwide covert environmental modification (geoengineering) activities have been ongoing for several decades, citing numerous peer-reviewed scientific and medical articles and other sources in support of our allegation that such activities are causing innumerable harms to Earth’s systems. These harms include, but are not limited to, catastrophic loss of wildlife, aggravation of global warming and climate chaos; disruption of habitats; aggravation of droughts and concomitant degradation of agriculture; and depletion of stratospheric ozone, which exposes surface life to deadly solar ultraviolet radiation. In 1978 the United Nations (UN) oversaw the creation of the Convention on the Prohibition of Military or Other Hostile Use of Environmental Modification Techniques (ENMOD), a deliberately vague and deceitful international treaty that has served as a Trojan horse to provide a “legal” basis for subsequent worldwide geoengineering activities (as described herein). Since the creation of the UN Environmental Program (UNEP) in 1972, the UN and some of its other agencies, including the World Meteorological Organization (WMO), Intergovernmental Panel on Climate Change (IPCC), and the World Health Organization (WHO), has formally committed itself to the integrity of the planetary environment. We appeal to the International Criminal Court to render judgement in favor of the world’s individual citizens, whose fundamental rights have been abrogated by planetary geoengineering, as herein documented. We respectfully request the following relief from the International Criminal Court: 1) Immediate and permanent end to the ENMOD Convention; 2) Permanent global injunction on all activities undertaken under ENMOD’s authority; 3) Declassification of all documents related to ENMOD activities as well as making all such documents freely available to the world; 4) Establishment of a legal body, fashioned after the International Military Tribunal at Nuremburg, to hear evidence and render justice for planetary treason and crimes against humanity and the environment.